(untitled) (Research, Society and Development, 2021)
Peanuts (Arachis hypogaea L.) stored in an uncontrolled environment undergo constant interactions, spontaneous and inevitable, directly influenced by temperature and relative humidity, whose transformations occur the deterioration of lipids and constitutes one of the most important technical problems in the food industry. Depending on environmental conditions, the packaging of low permeability to water vapor to store the product is of great importance in the post-harvest stages, providing protection and minizing the interactions between product-environment. The study aimed to analyze the impact of different packaging materials on peanut storage. The experiment comparing the packages was carried out in a 2x4 factorial scheme, being two types of packaging (raphy and jute) and four storage periods (60, 120, 220 and 290 days), with four replications. Peanuts were stored in the form of complete pods and samples were kept under uncontrolled ambient conditions. The water contents of the bark and seed, the electrical conductivity and the germination speed index of the seeds were evaluated. The data were submitted to variance analysis and the means compared by the Tukey test, with 5% significance. The packaging in jute packaging provided better storage conditions in relation to the packaging of atrophy. The temperature and relative humidity affect the equilibrium humidity of stored peanut seeds.